La Inadecuada Vigilancia Y Supervisión Que Brinda El Servicio Nacional De Compras Públicas En Los Procesos De Contratación Bajo El Régimen Especial - Armijos Armijos, Nataly Gabriela (2023)
The subject of this research study is the inadequate surveillance provided by the National Public Procurement Service in the contracting processes under the Special Regime, which as we know the governing body in charge and that manages each of the contracting processes is the SERCOP, allowing the acquisition of goods, works or services through the various procedures created to bid or award any contract, through the administration and redistribution, which is intended with the implementation of the Constitution of 2008 and the creation of the National Public Procurement Service, The Special Regime of Contracting, which as we know, the governing entity in charge and manages each one of the contracting processes is SERCOP, allowing the acquisition of goods, works or services through the various procedures created to bid or award any contract, through the administration and redistribution, which is intended with the implementation of the Constitution of 2008 and the creation of the Organic Law of the National System of Public Contracting, which in agreement seek to seek efficiency in the administration of public resources to meet the needs of the community. The Special Procurement Regime, as its name indicates, is given for certain procurements, which must be described based on the reasons why they are subject to this type of procedure for each of the cases specified in Article 2 of the LOSNCP, Thus, I set myself the objective of identifying the main shortcomings regarding the monitoring and supervision that are generated in the contracting processes under the special regime by evaluating the various processes that have occurred in Ecuador, this based on the rules created to regulate procurement as the Constitution, the law and its regulations, for which the scientific, inductive, deductive, analytical, comparative methods were used, In order to find out where the problem originates in these contracts, we used a survey and an interview that allowed us to recognize that from a critical and practical point of view, legal professionals consider that these shortcomings occur, We also studied the most emblematic cases in contracting issues that have uncovered a large gap of distrust in each process and finally we made the conclusions we reached after all this research study, concluding that the control and supervision given by both SERCOP and the Comptroller General of the State in its internal and external audits in each contracting process should be restructured internally.